On the classification of the bee genus Manuelia (Hymenoptera: Apidae) - Engel, Michael S. (Acta entomologica slovenica (Ljubljana), 2012)
The classification of the monogeneric and relic xylocopine tribe Manueliini is briefly addressed. Two subgenera are recognized in Manuelia Vachal - Manuelia s.str., consisting of Manuelia gayi (Spinola), and Uliamane subgen. n., comprising M. postica (Spinola) as type species and M. gayatina (Spinola). Diagnoses for the subgenera are provided along with a key to these groups and detailed images for M. postica.
Keywords: Anthophila; Apoidea; Argentina; Chile; čebele; Čile; Manuelia; taksonomija; taxonomy; Xylocopinae